Anne of Green Gables - Montgomery, L. M. (Lucy Maud), 1874-1942 (Charming classics., 1999)
Anne, an eleven-year-old orphan, is sent by mistake to live with a lonely middle-aged brother and sister on a Prince Edward Island farm and proceeds to make an indelible impression on everyone around her.